3D Agro-ecological Land Use Planning Using Surfer Tool for Sustainable Land Management in Sumani Watershed, West Sumatra Indonesia - Aflizar, .; Idowu, Alarima Cornelius; Afrizal, Roni; Jamaluddin, .; Husnain, .; Masunaga, Tsugiyuki; Syafri, Edi; Muzakir, . (JOURNAL OF TROPICAL SOILS, 2013)
Estimation of soil erosion 3D (E3D) provides basic information that can help manage agricultural areas sustainably, which has not been sufficiently conducted in Indonesia. Sumani watershed is main rice production area in West Sumatra which has experienced environmental problem such as soil erosion and production problem in recent years. 3D Agro-ecological land use planning based on soil erosion 3D hazard and economic feasibility analyses consist of production cost and prize data for each crop. Using a kriging method in Surfer tool program, have been developed data base from topographic map, Landsat TM image, climatic data and soil psychochemical properties. Using these data, the Universal Soil Loss Equation was used for spatial map of soil erosion 3D and proposed a 3D agro-ecological land use planning for sustainable land management in Sumani watershed. A 3D Agro-ecological land use planning was planned under which the land use type would not cause more than tolerable soil erosion (TER) and would be economically feasible. The study revealed that the annual average soil erosion from Sumani watershed was approximately 76.70 Mg ha-1yr-1 in 2011 where more than 100 Mg ha-1yr-1 was found on the cultivated sloping lands at agricultural field, which constitutes large portion of soil erosion in the watershed. Modification of land use with high CP values to one with lower CP values such as erosion control practices by reforestation, combination of mixed garden+beef+chicken (MBC), terrace (TBC) or contour cropping+beef+chicken (CBC) and sawah+buffalo+chicken (SBC) could reduce soil erosion rate by 83.2%, from 76.70 to 12.9 Mg ha-1 yr-1, with an increase in total profit from agricultural production of about 9.2% in whole Sumani watershed.Key words: CP-values, Erosion 3D, land use, Surfer Tool, USLE [How to Cite: Aflizar, AC Idowu, R Afrizal, Jamaluddin, E Syafri, Muzakir, Husnain and T Masunaga. 2013. 3D Agro-ecological Land Use Planning Using Surfer Tool for Sustainable Land Management in Sumani Watershed, West Sumatra Indonesia. J Trop Soils 18 (3): 241-254. Doi: 10.5400/jts.2013.18.3.241][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.3.241]REEFERENCESAflizar, A Roni and T Masunaga. 2013. Assessment Erosion 3D hazard with USLE and Surfer Tool: A Case study of Sumani Watershed in West Sumatra Indonesia. J Trop Soil 18: 81-92 doi: 10.5400/jts.2012.18.1.81Aflizar, A Saidi, Husnain, Hermansah, Darmawan, Harmailis, H Soumura, T Wakatsuki and T Masunaga. 2010. Characterization of Soil Erosion Status in an Agricultural Watershed in West Sumatra, Indonesia. Tropics 19: 28-42.Agrell PJ, A Stam and GW Fischer. 2004. Interactive multiobjective agro-ecological land use planning: The Bungoma region in Kenya. Eur J Operat Res 158: 194-217Agus F, DK Cassel and DP Garrity. 1997. Soil-water and soil physical properties under countour hedgerow systems on sloping oxisols. Soil Till Res 40: 185-199.Blake GR and R Hartage. 1986. Bulk Density. In: A Klute (ed). Methods of Soil Analysis, Part 1. Physical and Minerological Methods. American Society of Agronomy and Soil Science Society of America, Madison, Wisconsin, p. 364-367. Brady NC and RR Weil. 2008. The Nature and Properties of Soils. Fourteenth edition reviced. Pearason International edition. Pearson education Japan. p. 121-171.Chris SR and H Harbor. 2002. Soil erosion assessment tools from point to regional scales-the role of geomorphologists in land management research and implication. Geomorphology 47: 189-209.Choudhury C, PM Chauhan, P Garg and HN Garg. 1996. Cost-Benefot ratio of triple pass solar air heates. Energy Convers Manage 37: 95-116. Crasswell ET, A Sajjapongse, DJB Hawlett and AJ Dowling. 1997. Agroforestry in the management of sloping lands in Asia and the Pacific. Agrofores Sys 38: 121-130.FAO [Food and Agriculture Organization]. 1993. Guidelines for Land Use Planning. FAO Development Series 1, FAO, Rome.FAO/IIASA [Food and Agriculture Organization/International Institute for Applied Systems Analysis]. 1991. Agro-Ecological Land Resources Assessment for Agricultural Development Planning; A Case Study of Kenya: Resource Database and Land Productivity. Main Report and 8 Technical Annexes. Rome, AGL-FAO. 9 vols. 1150 p. Gee GW and JW Bauder. 1986. Particle size analysis. In: A Klute (ed). Methods of soil Analysis, Part 1. Physical and mineralogical Methods, American Society of Agronomy and Soil Science Society of America, Madison, Wisconsin, pp. 399-404.Golden software. 2010. Surfer® 9 for windows. Golden, Colorado. Available online http://www.goldensoftware.com/products/surfer/surfer.shtml.Hammer WI. 1981. Second soil conservation consultant report AGOF/INS/78/006. Tech. Note No 10, Centre of Soil Research, Bogor.Irvem A, F Topaglu and V Uygur. 2007. Estimating spatial distribution of soil loss over Seyhan River Basin in Turkey. J Hydrol 336: 30-37.IITA [International Institute of Tropical Agriculture]. 1979. Selected Methods for Soils and Plant Analysis, Manual Series No. 1, IITA, Ibadan, Nigeria, pp. 70.Iwata T, S Nakano and M Inoue. 2003. Impact of past riparian deforestation on stream communities in a tropical rain forest in Borneo. Ecol Appl 13: 461-473.Karyono. 1990. Home garden in Java: their structure and function. In: Lan-dauer K, M Brazil (eds). Tropical Home Garden, The United Nations University Press, Tokyo, pp. 138-146.Kravchenko A and DG Bullock. 1999. A comparative study of interpolation method for mapping soil properties. Agron J 91: 393-400.Kusumandari A and BR Mitchell. 1997. Soil erosion and sediment yield in forest and agroforestry areas in West Java, Indonesia. J Soil Water Cons 52: 376-380.Lee BD, RC Graham, TE Lauren, C Amrhen and RM Creasy. 2001: Spatial Distribution of Soil Chemical condition in a serpentinitic Wetland and Surrounding Landscape. Soil Sci Soc Am J 65: 1183-1196.Margareth and Arens. 1989. World Bank Environmental Department Working paper No.18. The World Bank, Washington, DC.Paranginangin N, R Sakthivadivel, NR Scoot, E Kendy and TS Steenhuis. 2004. Water accounting for conjunctive groundwater/surface water management: case of the Singkarak-Ombilin River basin, Indonesia. J Hydrol 292: 1-22.Reeve RC. 1965. Particle-size Analysis. In: CA Black, DD Evans, JL White, Ensminger and FE Clark (eds). Methods of Soil Analysis Part 1. Physical and Mineralogical Methods, American Society of Agronomy, Madison, Wisconsin, pp. 528-530. Sarainsong F, K Harashima, H Arifin, K Gandasasmita and K Sakamoto. 2007. Practical application of a land resources information system for agricultural landscape planning. Landscpe Urban Plan 79: 38-52.Schob A, J Schmidt and R Tenholtern. 2006. Derivation of site-related measures to minimize soil erosion on the watershed scale in the Saxonian loess belt using the model erosion 3D. Catena 68: 153-160.Shi ZH, CF Cai, SW Ding, TW Wang and TL Chow. 2004. Soil conservation planning at the small watershed level using RUSLE with GIS: a case study in the Three Gorge Area of China. Catena 55: 33-48.Soil Survey Staff. 1990. Keys to Soil Taxonomy. Washington, DC: USDA Natural Resources Conservation Service. Available online ftp://ftp-fc.sc.egov.usda.gov/NSSC/Soil_Taxonomy/keys/1990_Keys_to_Soil_Taxonomy.pdf.Stevenson M and H Lee. 2001. Indicator of sustainability as a tool in agricultural development: portioning scientific and participatory processes. Int J Sustain Dev World Ecol 8: 57-56.Svoray T, P Bar and T Bannet. 2005. Urban land-use allocation in a Mediterranean ecotone: Habitat heterogeneity Model incorporated in a GIS using a multi-criteria mechanism. Landscape Urban Plan 72: 337-351.Takata Y, S Funukawa, J Yanai, A Mishima, K Akshalov, N Ishida and T Kosaki. 2008. Influence of crop rotation system on the spatial and temporal variation of the soil organic carbon budget in northern Kazakhstan. Soil Sci Plant Nutr, 54: 159-171.Wakatsuki T, Y Shinmura, E Otoo and GO Olaniyan. 1998. African-based paddy field system for the integrated watershed management of the small inland valley of West Africa. FAO Water Report no. 17. pp. 5-79.Wischmeier WH and DD Smith. 1978. Predicting rainfall erosion losses: a guide to conservation farming, USDA Handbook: No. 537 US Department of Agriculture, Washington, DC pp 1-58.World Bank. 1989. World Bank Technical Paper Number 127. In: Doolette JB and WB Magrath (eds). Watershed Development in Asia. Strategies and Technologies Available online: http://www-wds.worldbank.org/external/default/WDSContentServer/WDSP/IB/1999/09/17/000178830_98101904135527/Rendered/INDEX/multi_page.txt.Zhang Y, H Yang, M Du, X Tang, H Zhang and B Peng. 2003. Soil erosion study on hillside in Southern Jiangsu province the cesium-137 tracer technique. Soil Sci Plant Nutr 49: 85-92.